2018
DOI: 10.1103/physrevfluids.3.023301
|View full text |Cite
|
Sign up to set email alerts
|

Viscoplastic squeeze flow between two identical infinite circular cylinders

Abstract: Direct numerical simulations of closely interacting infinite circular cylinders in a Bingham fluid are presented, and results compared to asymptotic solutions based on lubrication theory in the gap. Unlike for a Newtonian fluid, the macroscopic flow outside of the gap between the cylinders is shown to have a large effect on the pressure profile within the gap and the resulting lubrication force on the cylinders. The presented results indicate that the asymptotic lubrication solution can be used to predict the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Coarsegrain approaches for Newtonian fluids use lubrication force models as sub-grid-scale models for the under-resolved particle interactions. However, the authors recently found that such lubrication models cannot be straightforwardly applied in cases where particles are strongly confined in their yield envelopes such as may occur in sedimentation without imposed shear [26]. This necessitates direct numerical simulation.…”
Section: Mathematical Formulation and Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coarsegrain approaches for Newtonian fluids use lubrication force models as sub-grid-scale models for the under-resolved particle interactions. However, the authors recently found that such lubrication models cannot be straightforwardly applied in cases where particles are strongly confined in their yield envelopes such as may occur in sedimentation without imposed shear [26]. This necessitates direct numerical simulation.…”
Section: Mathematical Formulation and Solutionmentioning
confidence: 99%
“…In order to make the larger problem sizes considered in this study tractable we adopt a quasi-steady approximation, as in [14], and employ an overset grid discretization strategy. The grid generation procedure is discussed at length in [36,37], and has been used for Newtonian and viscoplastic particulate flow problems by the authors in [26,38]. The resultant linear system is inverted using the MUMPS massively parallel direct linear solver library [39].…”
Section: Mathematical Formulation and Solutionmentioning
confidence: 99%
“…Jossic and Magnin produced some results [32] of two Modelling and Simulation in Engineering cylinders by fixing the range of the Bingham number up to 40. Recently, Koblitz et al [33] investigated the hydrodynamic forces for very high values of Bn. Calder and Yezzi [34] considered a rate of convergence and application for obstacle problems.…”
Section: Outletmentioning
confidence: 99%
“…They also investigated the influence of the slip condition on the drag forces. In the recent research, Koblitz et al [25] presented the results of DNS simulations of interacting circular cylinders in three different cases whereas a Bingham fluid was changed between 0-2000 and the separation distance was kept constant at 1% of the cylinder radius in which the flow type was so called squeeze flow. They showed that the asymptotic lubrication solution is used in presence of the macroscopic flow assumption.…”
Section: Of 13mentioning
confidence: 99%